2023
DOI: 10.3390/plants12183276
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Chokeberry (Aronia melanocarpa) Fruits as Valuable Additive in Extruded Snack Pellets: Selected Nutritional and Physiochemical Properties

Agnieszka Wójtowicz,
Maciej Combrzyński,
Beata Biernacka
et al.

Abstract: In this paper, the nutritional value and (selected) physiochemical properties of extruded snack pellets enriched with fresh chokeberry (Aronia melanocarpa) fruits were analyzed from the perspective of being a new product for the functional food sector. The purpose of this study was to determine the effect of the addition of fresh chokeberry and variation in content and screw speed on extruded snack pellet basic compositions, fatty acid profiles, antioxidant activity, as well as water absorption and solubility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The effect of working screw speed on the WSI was clearly expressed at high level of feed moisture than at low level, where the effect was invisible. The increase in the screw speed led to stronger shear forces during the extrusion process, thus making the processed components more fragmented and much easier to elute [7]. The WSI varied from 22.3 to 26.4% of extrudates from chokeberry pomace with the twin screw extruder [24].…”
Section: Water Solubility Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of working screw speed on the WSI was clearly expressed at high level of feed moisture than at low level, where the effect was invisible. The increase in the screw speed led to stronger shear forces during the extrusion process, thus making the processed components more fragmented and much easier to elute [7]. The WSI varied from 22.3 to 26.4% of extrudates from chokeberry pomace with the twin screw extruder [24].…”
Section: Water Solubility Indexmentioning
confidence: 99%
“…Our values were higher, from 4.28 g/g to 6.56 g/g, which can be explained by the use of rice as main raw material for extrusion in our study. Wójtowicz et al [7] found that the increase in chokeberry amount in the initial mixture increased the water absorption of the snack pellets. This is in accordance with our results and can probably be explained by the increase in the number of components able to absorb water, like fibers and proteins [43].…”
Section: Water Absorption Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Native Americans used A. melanocarpa berries for food and medicinal application, in particular as an infusion to treat colds, while the bark was used as an astringent [ 5 , 8 , 9 ]. The A. melanocarpa edible black berries (diameter of about 1 cm), characterized by a little sour and astringent flavor [ 5 , 8 ], are used in the food industry for the production of syrups, juices, jams, and jellies (thanks to the presence of pectin), preserves, purees, nectars, wines, schnapps, tinctures, fruit infusions (tea), baked products, fruit desserts, and food supplements [ 5 , 6 , 8 , 9 , 10 , 11 ]. The harvest of chokeberries is generally performed during August and September [ 5 , 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A. melanocarpa berries are widely recognized as a valuable source of bioactive phenolic compounds such as flavonoids (mainly anthocyanins, proanthocyanidins, flavanols, and flavonols), phenolic acids (chlorogenic, neochlorogenic, caffeic), and tannins [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Polyphenolic compounds represent the most important constituents of black A. melanocarpa berries, accounting for 10.6–197.0 mg/g dry weight (dw) and 6.9–25.6 mg/g fresh weight (fw) as gallic acid equivalents [ 5 , 8 ], and the water-soluble pigment anthocyanins are responsible for the characteristic chokeberry black and dark blue/violet color [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%